PENGGUNAAN MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MENULIS DAN MEMBACA SISWA MATERI KELUARGA UNIK PADA KELAS II SD NEGERI SINDURJAN - Fitri, Nova Juwita; Pusporini, Ira Herawati Widyasari; Eviyanti, Eviyanti; Ngazizah, Nur (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Reading and writing skills are essential skills in education. Reading skills involve understanding texts, while writing skills include organizing ideas and information. This study aims to improve the reading and writing skills of grade II students of SD Negeri Sindurjan by using flashcard learning media. The study method used in this study is PTK (Classroom Action study). Data collection techniques used are observation and interviews. The provision of action using flashcard media was carried out on grade II students at SD Negeri Sindurjan who had problems with low writing and reading skills. At the pre-cycle stage, the average value of grade II was only 56.7, and the classical completeness was only 42.11%. Using flashcard media given to grade II at SD Negeri Sindurjan improved student learning outcomes in each cycle. In cycle I, classical learning completeness became 68%; in cycle II, classical learning completeness became 78%.